We loved it all : a memory of life - Millet, Lydia, 1968- (W.W. Norton & Company, Inc, 2024)
"A personal evocation of the glory of nature, our vexed position in the animal kingdom, and the difficulty of adoring what we destroy. Acclaimed novelist Lydia Millet's first work of nonfiction, We Loved It All, is a genre-defying tour de force that makes an impassioned argument for people to see their emotional and spiritual lives as infinitely dependent on the lives of nonhuman beings. Drawing on a quarter-century of experience as an advocate for endangered species at the Center for Biological Diversity, Millet offers intimate portraits of what she calls "the others"--the extraordinary animals with whom we still share the world, along with those already lost. Humans, too, fill this book, as Millet touches on the lives of her world-traveling parents, fascinating partners and friends, and colorful relatives, from diplomats to nut farmers--all figures in the complex tapestry each of us weaves with the surrounding world. Written in the tradition of Annie Dillard or Robert Macfarlane, We Loved It All is an incantatory work that will appeal to anyone concerned about the future of life on earth--including our own"--